Saúde mental dos negociadores militares - Teixeira, Marcos Eduardo da Silva (2022)
The Police Negotiator acts in the intervention in critical incidents, such as occurrences with hostages and suicide attempts, aiming at solving these events through verbalization. Acting in this scenario, in which the risk to the lives of all those involved is imminent, can cause damage to the health of these professionals. This research sought to investigate the mental health conditions of military police negotiators. Two surveys were carried out, whose method used has a mixed design, and the study was divided into two parts. Study 1 involved a national survey, using quantitative techniques, applied to negotiators from the Military Police of the states of Ceará, Federal District, Espírito Santo, Rio de Janeiro, Mato Grosso do Sul, Pernambuco, Paraná and São Paulo, where it was investigated the mental health of negotiators. This study used an online questionnaire consisting of the Depression, Anxiety and Stress Scale - Short Form (DASS-21), the Work and Illness Risks Inventory (ITRA), and a sociodemographic questionnaire, in addition to questions related to the topic. Study 2 investigated how PMES Negotiators assess their preparation, the way they organize their work, their established relationships with the PMES corporation and the factors that may contribute to their health and illness. This study used qualitative techniques. Data were collected with the aid of a semi-structured interview, and were submitted to content analysis. The theoretical support of the research was Ergology. The results showed that the health conditions of the negotiators from the participating states did not show a prevalence of depression, anxiety and stress and that the activity carried out by the PMES Police Negotiator generates negative effects on the health of this worker. It was concluded that further studies are needed to expand the information on the subject, as well as guide possible measures that are beneficial to the military police worker who works in this very specific area.